Law's Order : What Economics Has to Do with Law and Why It Matters - Friedman, David D. (Book collections on Project MUSE., 2000)
What does economics have to do with law? Suppose legislators propose that armed robbers receive life imprisonment. Editorial pages applaud them for getting tough on crime. Constitutional lawyers raise the issue of cruel and unusual punishment. Legal philosophers ponder questions of justness. An economist, on the other hand, observes that making the punishment for armed robbery the same as that for murder encourages muggers to kill their victims. This is the cut-to-the-chase quality that makes economics not only applicable to the interpretation of law, but beneficial to its crafting. D.